Development and Validation of Pedagogical Beliefs About Teaching Practices Questionnaire: A Cross-Continental Study - Moliner, Lidon; Sanahuja, Aida; Alegre, Francisco (Pedagogika, 2023)
The aims of this study were to create and validate a questionnaire designed to assess schoolteachers’ pedagogical beliefs according to 641 schoolteachers and 26 experts and analyse the results obtained therefrom. A seven-factor structure was defined for the questionnaire, and Cronbach’s alpha was .91. Compared to their older, more experienced and male counterparts, younger, less experienced and female teachers, respectively, demonstrated more positive beliefs about factors such as classroom climate, the teacher’s role and the student’s role.